2012
DOI: 10.1016/j.neuroimage.2012.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Examining ERP correlates of recognition memory: Evidence of accurate source recognition without recollection

Abstract: Recollection is typically associated with high recognition confidence and accurate source memory. However, subjects sometimes make accurate source memory judgments even for items that are not confidently recognized, and it is not known whether these responses are based on recollection or some other memory process. In the current study, we measured event related potentials (ERPs) while subjects made item and source memory confidence judgments in order to determine whether recollection supported accurate source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
199
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(235 citation statements)
references
References 87 publications
(159 reference statements)
32
199
4
Order By: Relevance
“…In the same direction, a number of studies have observed that when item-source associations can be processed together at encoding, familiarity processes are also enhanced during recognition. Thus, when item and source information are encoded in the same modality (visual) vs. different modality (visual and auditory;Tibon, Ben-Zvi, et al, 2014;Tibon, Gronau, et al, 2014;Tibon & Levy, 2014), when the nature of the association item-source is intrinsic versus extrinsic (Ecker et al, 2007a, b;Zheng et al, 2015), or when source refers to salient contextual information (Mollison & Curran, 2012), source recognition prompts larger familiarity-related ERPs, suggesting that memory for source information is strengthened (Addante et al, 2012;Chiu et al, 2013;Curran, 2004). In the present study, no explicit instructions for unitization were given; however, as commented above, we promoted item-context binding processes at encoding.…”
Section: Discussionmentioning
confidence: 99%
“…In the same direction, a number of studies have observed that when item-source associations can be processed together at encoding, familiarity processes are also enhanced during recognition. Thus, when item and source information are encoded in the same modality (visual) vs. different modality (visual and auditory;Tibon, Ben-Zvi, et al, 2014;Tibon, Gronau, et al, 2014;Tibon & Levy, 2014), when the nature of the association item-source is intrinsic versus extrinsic (Ecker et al, 2007a, b;Zheng et al, 2015), or when source refers to salient contextual information (Mollison & Curran, 2012), source recognition prompts larger familiarity-related ERPs, suggesting that memory for source information is strengthened (Addante et al, 2012;Chiu et al, 2013;Curran, 2004). In the present study, no explicit instructions for unitization were given; however, as commented above, we promoted item-context binding processes at encoding.…”
Section: Discussionmentioning
confidence: 99%
“…Addante, Ranganath, & Yonelinas, 2012). For instance, Peters and Daum (2009) reported a more positive FN400 for correct relative to incorrect source retrieval and for incorrect trials relative to correct rejections.…”
Section: Introductionmentioning
confidence: 93%
“…This type of source identification evoked potentials that dissociated from those evoked by an old/new test at frontal electrode sites after about 400 msec. Other typical tasks tested the ability to indicate whether a visually presented word had previously been heard from a male or female voice or what type of decision one had to make while incidentally learning words (Addante, Ranganath, & Yonelinas, 2012). Evoked potentials revealed frontal old/new effects starting after 400 msec, called FN400, whose amplitude, depending on the study, varied with accuracy or confidence about the source judgment (Addante et al, 2012;Leynes & Phillips, 2008;Vallesi & Shallice, 2006;Wilding & Rugg, 1996).…”
Section: Introductionmentioning
confidence: 99%